A highly selective and sensitive fluorescent chemosensor for Zn2+ based on a diarylethene derivative. Issue 79 (27th October 2017) - Feng, Erting; Tu, Yayi; Fan, Congbin; Liu, Gang; Pu, Shouzhi
Abstract : A promising photochromic fluorescent chemosensor1o linked with Schiff base unit was synthesized and the sensitivity test of1o toward Zn 2+ has been performed with detection limit up to 8.10 × 10 −8 M without any interference from Cd 2+ . Abstract : A promising photochromic fluorescent chemosensor1o linked with Schiff base unit was synthesized. It displayed outstanding photochromism and a superb fluorescence turn-on response toward Zn 2+ . Upon the addition of Zn 2+ to1o, the fluorescent color of the solution obviously changed from blue to bright green with a 27-fold fluorescent intensity increase. The combination of1o –Zn 2+ with 1 : 1 stoichiometry was verified by Job's plot and MS analysis. The detection limit for1o toward Zn 2+ was measured to be 8.10 × 10 −8 M. Furthermore, logic gate research was established with Zn 2+, UV and visible light as input signals and the emission intensity as the output signal.